Influence of long-term tillage and diversified cropping systems on hydro-physical properties in a sandy loam soil of North-western India - Patra, S.; Parihar, Chiter Mal; Mahala, Deep Mohan; Singh, D.; Nayak, Harisankar; Patra, K.; Reddy, K. S.; Pradhan, S.; Sena, Dipaka Ranjan (Elsevier, 2023)
A study was conducted to determine the combined effects of three tillage practices and four maize (Zea mays L.)- based cropping systems on physical, saturated, and near-saturated hydraulic properties in a sandy loam soil of North-Western India. Split-plot experimental design was adopted with tillage [conventional tillage (CT), zero tillage (ZT), and permanent raised bed (PB)] as the main plot treatments and intensified crop rotations [Maize (Zea mays L.)-Wheat (Triticum aestivum)-Greengram (Vigna radiata L.) (MWGg), Maize-Chickpea (Cicer arietinum L.)-Sesbania (Sesbania aculeata) (MCpSb), Maize-Mustard (Brassica juncea) -Greengram (MMuGg) and MaizeMaize-Sesbania (MMSb)] as subplot treatments. The saturated and near-saturated soil hydraulic conductivity were derived from steady-state infiltration rates measured using a hood infiltrometer on the surface soil at 0, - 1, and - 3 cm pressure heads. The long-term (10 years) study revealed that the bulk density (BD) of the soil under conservation agriculture (CA) practices (PB and ZT) was significantly (P = 0.05) lower than that in CT practices. The soil BD in the MCpSb cropping system was measured to be the lowest (1.24 g cm- 3 ) among all the cropping systems. The soil aggregate mean weight diameter (MWD) under PB and ZT was determined to be 31% and 27% higher than in the CT treatments. In tillage × cropping systems interactions, the highest MWD was observed in the PB×MWGg. The saturated and near-saturated hydraulic conductivity (K(h)) were estimated to have higher values in CA practices (PB and ZT) than in the CT treatments. In the case of cropping systems, the soil’s mean field saturated hydraulic conductivity was estimated to be significantly (P < 0.05) higher under the MWGg, MCpSb, and MMuGg than the MMSb. The present study indicates that conservation agriculture-based crop management with diversified maize-based rotation (MCpSb, MWGg, and MMuGg) could be promising alternatives to conventional tillage practices (CT). Among the cropping system choices, MWGg was more effective in improving the soil’s hydro-physical properties in the study area.